Mycoplasma pneumoniae induces allergy by producing P1-specific immunoglobulin E - Ye, Qing; Mao, Jian-hua; Shu, Qiang; Shang, Shi-qiang (Annals of allergy, asthma, & immunology, 2018)
Our previous study found that most Mycoplasma pneumoniae (MP) pneumonia (MPP)patients had elevated serum total immunoglobulin E (IgE) levels. To determine components of MP that can cause an IgE increase in children, and to clarify its specific mechanism. The components of MP cells were isolated by serum IgE from patients with MP pneumonia. These components obtained through the prokaryotic expression were used as allergens to detect the proportion of allergen-specific IgE produced in MPP patients, and the clinical characteristics and related immune parameters of these patients who produced this allergen-specific IgE were also analyzed. In addition, a cell experiment was used to verify the biological effect of these components in vitro. P1-specific IgE was detected in serum of MPP children. An approximately 24-kDa polypeptide of P1 protein was obtained through prokaryotic expression purified by nickel agarose affinity chromatography. Approximately 9.2% of MPP patients produced IgE against this polypeptide of P1 protein, which was more likely to be produced in MPP patients with no history of allergies or family history of allergy-related diseases. P1-specific IgE-positive MPP patients had more severe clinical symptoms, with excessive secretion of interleukin (IL)-4 and IL-5 and overdifferentiation of Th0 cells into Th2 cells. Tests also demonstrated that the P1 protein stimulated excessive secretion of IL-4 and IL-5 in peripheral blood mononuclear cells from the peripheral blood of healthy donors. Mycoplasma pneumoniae is not only an infectious agent but also an allergen for certain individuals. The P1 protein of MP can induce the production of P1-specific IgE.